(untitled) (Global Journal of Medical Research, 1970)
As localized neuropathic pain can seriously decrease quality of life, physicians are challenged to look for treatment modalities which are easy to apply, safe and effective. Over the last decade, isotonic glucose (or dextrose) injections have received more attention among clinicians worldwide. In this article, the focus is on the application of intradermal injections of glucose 5%. Glucopuncture is especially interesting for doctors and patients who live in remote areas where pain medications are not available, or too expensive.